Unidentified dengue serotypes in DENV positive samples and detection of other pathogens responsible for an acute febrile illness outbreak 2016 in Cajamarca, Peru - Del Valle-Mendoza, Juana (2020)
Objective: To describe the prevalence of dengue virus serotypes, as well as other viral and bacterial pathogens that cause acute febrile illness during an outbreak in Cajamarca in 2016. Results: Dengue virus (DENV) was the most frequent etiologic agent detected in 25.8% of samples (32/124), followed by Rickettsia spp. in 8.1% (10/124), Zika virus in 4.8% (6/124), Chikungunya virus 2.4% (3/124) and Bartonella bacilliformis 1.6% (2/124) cases. No positive cases were detected of Oropouche virus and Leptospira spp. DENV serotypes identification was only achieved in 23% of the total positive for DENV, two samples for DENV-2 and four samples for DENV-4. During the 2016 outbreak in Cajamarca-Peru, it was observed that in a large percentage of positive samples for DENV, the infecting serotype could not be determined by conventional detection assays. This represents a problem for the national surveillance system and for public health due to its epidemiological and clinical implications. Other viral and bacterial pathogens responsible for acute febrile syndrome were less frequently identified.